Pembelajaran Terpadu Dalam Perspektif K.H. Ahmad Dahlan - Pera Ika Fidayanti (Institut Agama Islam Negeri (IAIN) Curup, 2020)
K.H. Ahmad Dahlan compiled Islamic education institutions in Indonesia which involved several factors, one of which was due to K. H. Ahmad Dahlan's concerns against indigenous Muslims, facilitating religious science education and general science. The purpose of this study was to study K. H. Ahmad Dahlan's educational concepts and question K. H. Ahmad Dahlan's educational philosophy. This research method is literature study (library research). The results of this study discuss the concept of K. H. Ahmad Dahlan's education, namely the integration of science and religion, the integration of religious science and general science, and freedom of thought. Furthermore K. H. Ahmad Dahlan's educational philosophy is the first, the highest knowledge can be achieved through common sense and istiqamah towards the truth of reason and based on a pure heart. Second, reason is a basic human need. Third, the science of mantiq or logic is the highest education for humans which can only help if humans escape God's guidance.